2003
DOI: 10.1113/jphysiol.2003.042242
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid1 Receptor in the Dorsal Vagal Complex Modulates Lower Oesophageal Sphincter Relaxation in Ferrets

Abstract: Delta 9-tetrahydrocannabinol (D 9 -THC), the active constituent of marijuana, and endogenous cannabinoid receptor ligands (anandamide and 2-arachidonylglycerol) mediate their effects through specific receptors designated as the cannabinoid 1 (CB1) and cannabinoid 2 (CB2) receptors. The CB1 receptor and its mRNA are seen throughout the central nervous system (Matsuda et al. 1993;Tsou et al. 1998), whereas the CB2 receptor is found primarily in immune tissues (Berdyshev, 2000).The distribution of CB1 receptor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 31 publications
2
90
0
2
Order By: Relevance
“…Both AT 1 -and CB 1 -receptors were identified in the NTS, in the dorsal motor nucleus of vagus and in the paraventricular nuclei (Castelli et al, 2007;Partosoedarso et al, 2003;Seagard et al, 2004). On the basis of this findings it may be speculated that AT 1 receptorinduced activation of CB 1 receptors might take place in the dorsal vagal complex, however, whether there is an overlap in expression of CB 1 and AT 1 receptors in this brain area remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both AT 1 -and CB 1 -receptors were identified in the NTS, in the dorsal motor nucleus of vagus and in the paraventricular nuclei (Castelli et al, 2007;Partosoedarso et al, 2003;Seagard et al, 2004). On the basis of this findings it may be speculated that AT 1 receptorinduced activation of CB 1 receptors might take place in the dorsal vagal complex, however, whether there is an overlap in expression of CB 1 and AT 1 receptors in this brain area remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids were shown to inhibit gastrointestinal motility (Izzo et al, 1999;Krowicki et al, 1999), gastric acid secretion (Adami et al, 2002) and development of gastric mucosal lesions both in acid-dependent (Germano et al, 2001;Rutkowska and Fereniec-Goltbiewska, 2006) and acid-independent ulcer models (Shujaa et al, 2009). Accordingly, CB 1 receptors were identified in neurons of the enteric nervous system and in sensory terminals of vagal and spinal neurons, moreover, CB 1 receptors are also identified in the dorsal vagal complex: in the nucleus of the solitary tract (NTS) (Partosoedarso et al, 2003), in the dorsal motor nucleus of vagus (DMNV) (Mackie, 2005) and prominently, in the area postrema (Mackie, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several neuropeptides, and their receptors e.g. μ-opioid receptors [157][158][159]] NK 1 -receptors [160,161] angiotensin AT 1 receptors [162,163] TRH receptors [126,127,165], neuropeptide Y receptors [166,167] have been identified in this area, and activation of these receptors result in mucosal protection. Accumulating data suggest that in the periphery the final step in the chain of events of centrally initiated mucosal protective processes is the release of sensory neuropeptides, such as CGRP and partly somatostatin, from the capsaicin sensitive primary afferent neurons, as well as NO and prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
“…e.g. μ-opioid receptors (in NTS and DMNV) [157], cannabinoid receptors (CB 1 -receptors in NTS and DMNV and CB 2 -receptors in NTS and brain stem neurons) [158,159] NK 1 -receptors in NTS and DMNV) [160,161], angiotensin AT 1 receptors in in the NTS, area postrema and DMNV [162,163] can influence gastric mucosal homeostasis. Our experimental results demonstrated that opioid peptides [4,133], anandamide, 2-arachidonoyl glycerol (2-AG) endocannabinoids, ligands of cannabinoid CB 1 and CB 2 receptors [137,142], as well as (SP) [136] given i.c.v.…”
Section: Role Of Capsaicin Sensitive Afferent Fibers and In The Actiomentioning
confidence: 99%
“…[30][31][32][33] Bu sonuçlarla doğrultulu olarak sağlıklı gönüllülerde yapılan çalışmada, ∆ 9 -THC'nin geçici LES relaksasyon sayısını azalttığı ve asit reflü ataklarında anlamlı olmayan bir azalma sağladığı gösterilmiştir. 32 Hepsi birden değerlendi-rildiğinde, CB reseptör aktivasyonunu sağlayan ilaç-ların gastroözofageal reflü tedavisinde umut verici bir yeri olduğu düşünülmektedir.…”
Section: Alt öZofageal Sfi̇nkter (Les) üZeri̇ne Etki̇leri̇unclassified